2012
DOI: 10.1556/jep.10.2012.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Are costly apologies universally perceived as being sincere?

Abstract: Are costly apologies universally perceived as being sincere? : A test of the costly apology-perceived sincerity relationship in seven countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…One potentially productive avenue would be manipulating the real, or even perceived, cost of intergroup apologies for the apologizing group. Previous research has shown that costly apologies are more effective at eliciting forgiveness (Ohtsubo & Watanabe, 2009) across multiple cultures (Ohtsubo et al, 2012).…”
Section: Author Manuscriptmentioning
confidence: 99%
“…One potentially productive avenue would be manipulating the real, or even perceived, cost of intergroup apologies for the apologizing group. Previous research has shown that costly apologies are more effective at eliciting forgiveness (Ohtsubo & Watanabe, 2009) across multiple cultures (Ohtsubo et al, 2012).…”
Section: Author Manuscriptmentioning
confidence: 99%
“…However, there is an alternative explanation: compensation is effective because it allows the victim to recoup his/her losses, and equity is restored (Darley & Pittman, 2003). Nonetheless, Ohtsubo and Watanabe (2009, Studies 2 and 3) showed that apology cost that was unilaterally incurred by the perpetrator and would not be transferred to the victim (e.g., the perpetrator cancelling an important meeting) was also effective (see Ohtsubo et al, 2012, for replications in seven countries). Thus, without taking their signaling function into account, the effectiveness of costly forms of reparative acts cannot be fully understood.…”
Section: Relationship Value Exploitation Risk and Costly Apologymentioning
confidence: 99%
“…Based on costly signaling theory, receivers perceive costlier signals to be more credible and reliable (Gintis et al., 2001; Roberts, 1998; Smith & Bird, 2000; Sosis, 2000; Zahavi, 1977). Previous studies found when the wrongdoer was willing to bear more cost to apologize or compensate, the victim was more likely to feel their sincerity (Eaton, Struthers, & Santelli, 2006; Gauché & Mullet, 2005; Ohtsubo & Watanabe, 2009; Ohtsubo et al., 2012). It is possible that people consider self-punishment as a sincere expression of remorse due to the cost and forgive the wrongdoer.…”
Section: Introductionmentioning
confidence: 97%